Investigating the attributes of Chinese primary school adoption among the Malay community in Malaysia / Heng Buai Chin, Neo Yee Feng and Chan Jie Yan - Heng, Buai Chin; Neo, Yee Feng; Chan, Jie Yan (2021)
Around 100,000 non-Chinese students are studying in Sekolah Jenis Kebangsaan Cina (SJKC) schools every year in Malaysia. Most of them are Malays and Bumiputeras. Although there is some research on non-Chinese students in SJKCs, no research has taken place in Selangor. This study aims to investigate why Malay parents sent their children to SJKC and their expectations for their children's education in SJKC. This study also explored the academic achievement patterns and factors that affected students' learning outcomes. A total of 113 Malay students and 111 teachers from 5 selected SJKCs in Klang, Selangor, participated in this study. The data collection method used in this study included surveys, interviews, and content analysis. Descriptive statistics and qualitative approaches were used to analyse the data collected. The reason Malay parents in Klang sent their children to SJKC was more inclined to instrumental motivational factors. Malay parents wanted their children to master the Chinese language because of its high economic value, leading to better prospects in the future. The overall academic achievement of the Malay students in this study is less satisfactory. Lastly, the factors affecting students’ Chinese language acquisition included students’ academic ability, attitude and motivation. The external factors are the family's lack of a Chinese language environment, parents having low expectations, and a lack of spiritual and material support. The findings of this research will help Malay parents and teachers in SJKCs to have a better understanding of the learning situation of Malay students in SJKCs in Klang. Malay parents should give more attention and support their children's learning process in SJKCs, as early as possible.